EVALUASI PENCAPAIAN STANDAR PELAYANAN MINIMAL BERDASARKAN PRINSIP GOOD GOVERNANCE DI SEKOLAH DASAR NEGERI - Novita Wijanarti (Universitas Kristen Satya Wacana, 2016)
This study aimed to evaluate the achievement of Minimum Service Standards according to Minister of Education and Culture Act, Number 23/2013 based on the principles of Good Governance in SD Negeri 4 Kaliaman Jepara through discrepancy evaluation model. This study was evaluation research consisted of the definition phase, the instalation, process, and product. This research subject was the principal, teachers and students of six grade. Data source was obtained from 12 teachers including Principal and 35 students through interviews, questionnaires, and study of documents. Data collection techniques used were interviews, questionnaires, and observations. Data processing techniques performed by data classification, data presentation, and data verification. The data validity used triangulation of data. The results of this study indicated that the definition phase of the school had a vision in line with the objective of Minimum Service Standards program, supported by adequate human resources in terms of number of educators and educational qualifications as well as the infrastructure that supported understanding of the principles of Good Governance. In addition, the installation phase, had been carried out by looking at the expectations and activities that made the School Work Plan and saw the challenges facing schools with the implementation of the principles of Good Governance which was held on the activities of each type of service in the Minimum Service Standards. At the process phase, School Work Plan was already implemented based on the principles of Good Governance Implementation. At the product phase, it was seen from the Minimum Service Standards data achievement and implementation of the principles of good governance were equally obtained good category. The Minimum Service Standards attainment of the six types of services was 87.4%, gained good criteria (B) and the implementation of the principle of good governance to the implementation was 87.5% with good criteria (B). The program is still feasible to proceed because the Minimum Service Standards program that has been made reached and acquired good categories.